Ketika Self-Compassion Bertemu Peran Ayah: Kunci Regulasi Emosi Generasi Z di Karawang - Siti Nurhaliza; Nur Ainy Sadijah; Regi Ramadan (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Generation Z is deeply engaged with social media, which not only plays a role in the formation of personal identity but also serves as a significant source of emotional stress. This study aims to examine the influence of self-compassion and father involvement on emotional regulation among Generation Z in Karawang. A quantitative approach with a causal design was used in this study, which involved 204 participants. The research instruments used were the Emotion Regulation Questionnaire (ERQ) to assess emotion regulation, the Self-Compassion Scale (SCS) to assess self-compassion, and the Reported Father Involvement Scale (FIS-R) to assess father involvement. The results of the simultaneous test showed a positive and significant effect (Sig. 0,000). Based on the positive unstandardized beta coefficients, it can be concluded that high levels of self-compassion and father involvement result in high levels of emotion regulation among Generation Z in Karawang. The overall effect size was 51,6%. The resulting, categorization indicates that self-compassion falls within the moderate range, father involvement within the low range, and emotion regulation within the high range. This study aims to deepen understanding of self-compassion and the role of fathers in fostering positive and adaptive emotional regulation among Generation Z.